Combustion of 'as recieved' palm kernel shell in a bubbling fluidized bed combustor (2012)
"Low cost and minimum emission of green house gases are two of the key advantages of using agricultural wastes as fuel in a bubbling fluidized bed combustor; however this advantage could be neutralized if significant cost and energy is spent on processing prior to usage of the waste, therefore if processing stage could be. circumvented without compromising effectiveness and efficiency, a substantial operational cost saving could be achieved when using biomass as fuel in a commercial scale bubbling fluidized bed combustor (BFBC). This research focus on use of 'as received' Palm kernel shell (PKS) in an experimental model bubbling fluidized bed combustor (BFBC). PKS feedstock received from the farm were cornbusted in several experiments in a 150mm diameter experimental model BFBC. The effect of large particle size feedstock of the 'as received'(4-22mm) on thermal profile and emission characteristics during the combustion process were examined. Operational chalienges such as fuel feeding, start-up and de-fluidization is examined and compare to situation when pulverized biomass is used. An electronic based inert bed temperature regulating unit ensure that the bed temperature is maintained at the pre-set value of 750°C in all the experiments. It was noted that combustion and emission characteristics with 'as received' PKS compare favourably with that of pulverized, however it was discovered that for specific feed rate( fd) and fluidizing air velocity.) the frequency at which the inert bed temperature regulating unit cut-off is higher for the 'as received'. The results indicate that PKS sample obtainable from Nigeria farms could be fired directly to generate energy in bubbling fluidized bed combustor. "